Morphology of the brain base arteries of the giant anteater (Myrmecophaga tridactyla) (Bioscience Journal, 2023)
This study aimed to describe the brain base arteries of the Myrmecophaga tridactyla using ten cadavers of adults from this species, including five male and five female specimens. The arterial vascular bed was perfused via the thoracic aorta with a dyed natural latex solution, and the animals were fixed and preserved with a 10% formaldehyde buffered solution. The encephala were removed, and their vessels dissected. Basilar artery formation occurred by anastomosis of the thick ventral spinal artery with vertebral arteries. The basilar artery formed two arterial islands and gave bulbar and pontine branches, and cranial, middle, and caudal cerebellar arteries and ended by forking into its terminal branches, the caudal communicating arteries. The blood supply of the encephalon derived solely from the vertebrobasilar system, and the arterial circle of the brain was closed caudally and rostrally. The absence of participation of internal carotid arteries in encephalon irrigation, the island formations by the basilar artery, and the fusiform shape of the arterial circle of the brain are peculiar characteristics of the vascular anatomy of the brain base of M. tridactyla.